AKTIVITAS ANTIBAKTERI NANOPARTIKEL PERAK HASIL BIOSINTESIS Plantago major L.: KAJIAN BIOLOGIS DAN IMPLIKASINYA DALAM PEMBELAJARAN KONTEKSTUAL - Saefi, Muhammad; Adi, Widi Cahya; Pamungkas, Rahmania; Sudrajat, Ahmad Kamal; Setiawan, M. Eval (FKIP Universitas Tanjungpura, 2025)
Science learning in higher education is often detached from students' cultural context, thus reducing the relevance of the material and scientific concepts being learned. This study aims to examine how student involvement in a biosynthesis experiment of silver nanoparticles (AgNPs) from Plantago major L. and its antibacterial activity testing can improve students' understanding and attitudes regarding cultural context and science content. The study used a mixed-methods approach involving 34 Biology students in a series of laboratory activities, pretest-posttest knowledge evaluations, and narrative reflections. The characterization results showed an absorbance peak of AgNPs at 460 nm and indicated nanoparticles with uniform size. Meanwhile, AgNPs showed higher antibacterial activity against Staphylococcus aureus than Salmonella typhi. Bayesian paired t-test analysis showed a significant increase in students' knowledge scores, and narrative reflections revealed a strengthening of attitudes towards recognizing culture as a source of science learning. These findings indicate that local resource-based laboratory learning activities are not only biologically relevant but also effective in shaping students' scientific understanding and are culturally meaningful.